In search of charismatic leaders or: You get what you ask for - Nada Endrissat; Werner R. Müller; Andreas Jaeger Fontana (Universität Basel, Wirtschaftswissenschaftliches Zentrum (WWZ), 2006)
The Global Leadership and Organizational Behavior Effectiveness (GLOBE) study is currently the most comprehensive research endeavor that set out to answer - amongst others - whether or not charismatic/value-based leadership is universally seen to contribute to effective leadership. The results have been appearing in various journals and books supporting this assumption and conveying the image that charismatic leaders are worldwide successful. Given the study's scope and exemplary status we suspect that the aforementioned result will receive the status of a 'given fact' if the study is not critically reviewed. The paper strives to fulfill this call by taking a 'closer look' at the conception of charisma in today's charismatic leadership theories as well as the GLOBE study, its results and interpretation. We argue that the items that are universally endorsed are not primarily pertaining to charisma but rather represent common, positive connoted leadership attributes. Moreover, the paper proposes an alternative to the research approach adopted by GLOBE, i.e. we present a qualitative leadership study and its result and will discuss whether or not charismatic leadership can be found in the German-speaking part of Switzerland. Our conclusion suggests that the answer to this question is dependent upon the adopted research approach. The paper closes by outlining implications and encouraging critical reviews of established research results.
Keywords: 330; leadership; critical review; research methods; social constructionism